Digitizing counselling practice: A study of student values and challenges associated with traditional face-to-face counselling and e-counselling modes - Patricia Mawusi Amos (Journal of Pedagogical Research, 2022)
It is common knowledge that face-to-face counselling is practiced in every country. Conversely, e-counselling is offered in many countries even though some experts disagree with its effectiveness and ethicality. The study, thus, purposed to gain a deeper understanding of students' values and challenges of face-to-face and e-counselling in Ghanaian universities. Therefore, a cross-sectional survey design was adopted. A standardized instrument: Online and Face-to-face Counselling Attitudes Scales, and a Satisfaction Questionnaire were adapted for the data collection. T-test and multiple linear regression were used to analyse data set from 384 students. Findings revealed that although technological devices are largely accessible, students value face-to-face counselling than e-counselling. However, their inclination to e-counselling cannot be overlooked. Also, there was no significant difference in students' values to e-counselling for gender. Again, the male students value face-to-face counselling more as compared to female students. The multiple regression revealed that values of face-to-face and e-counselling predicated satisfaction to face-to-face and e-counselling respectively. It is recommended that university counselling practitioners should enhance the use of face-to-face counselling and train in e-counselling so that students will be offered options in counselling services.